Identification of candidate SNPs associated with embryo mortality and fertility traits in lactating Holstein cows - Gonzalez Berrios, Carolina L.; Bowden, Courtney F.; Saad, Hamad M.; Bishop, Jeanette V.; Van Campen, Hana; Pinedo, Pablo; Hansen, Thomas R.; Thomas, Milton G. (Frontiers in Genetics, 2024)
Targeted single nucleotide polymorphisms (SNPs) have been used in genomic prediction methodologies to enhance the accuracy of associated genetic transmitting abilities in Holstein cows. The objective of this study was to identify and validate SNP associated with fertility traits impacting early embryo mortality. The mRNA sequencing data from day 16 normal (n=9) and embryo mortality (n=6) conceptuses from lactating multiparous Holstein cows were used to detect SNPs. Selection of specific genes with SNP as preliminary candidates were based on associations with reproductive and fertility traits. Validation of candidate SNP and genotype to phenotype analysis were conducted in a separate cohort of lactating primiparous Holstein cows (n=500). After genotyping, candidate SNP were filtered using a quality control pipeline via PLINK software.Continuous numeric and binary models from reproductive traits were evaluated using the mixed procedure for a generalized linear model-one way ANOVA or logistic regression, respectively.Sixty-nine candidate SNPs were initially identified, but only 23 passed quality control procedures.Ultimately, the study incorporated 466 observations for statistical analysis, after excluding animals with missing genotypes or phenotypes. Significant (P<0.05) associations with fertility traits were identified in seven of the 23 SNP: DSC2 (cows at 1st calving were older with A allele); SREBF1 and UBD (cows took longer to conceive with T or G allele, respectively); DECR1 and FASN (cows were less likely to become pregnant at first artificial insemination with C allele); SREBF1 and BOLA-DMB (cows were less likely to be pregnant at 150 days in milk with T allele). It was also determined that two candidate SNPs within the DSC2 gene were tag SNPs. Only DSC2 SNP had an important allele substitution effect in cows with the G allele by having a decreased age at first calving by 10 days. Candidate SNPs found in this study could be used to develop genetic selection tools to improve fertility traits in dairy production systems.